Death of Kings a novel - Cornwell, Bernard (New York : HarperCollins, 2011)
The fate of a young nation rests in the hands of a reluctant warrior in the thrilling sixth volume of the New York Times bestselling Saxon Tales series. Following the intrigue and action of The Burning Land and Sword Song, this latest chapter in Bernard Cornwell's epic saga of England is a gripping tale of divided loyalties and mounting chaos. At a crucial moment in time, as Alfred the Great lays dying, the fate of all--Angles, Saxons, and Vikings alike--hangs desperately in the balance.
Keywords: Alfred, -- 849-899; Great Britain -- History -- Alfred, 871-899; Great Britain -- History -- Anglo-Saxon period, 449-1066; Historical fiction